THE ANTIOXIDANT STUDIES OF TWO MEDICINAL PLANTS, SPHAERANTHUS INDICUS AND PSOPHOCARPUS TETRAGONOLOBUS - N, Vijayalakshmi; Krishna Rao, Mudiganti Ram (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study deals with the antioxidant assays of the different leaf extracts of two medicinal plants, Sphaeranthus indicus and Psophocarpus tetragonolobus. Methods: Dried leaves of S. indicus and P. tetragonolobus were packed in separate round bottom flasks for sample extraction using ethanol, methanol, hexane, and distilled water as solvents for 72 h, and the extracts were collected after evaporating the solvents. Antioxidant studies of the various extracts were performed by 1-diphenyl-2-picrylhydrazyl and Ferric Reducing Ability of Plasma assays. Results: Among the two plants studied, S. indicus showed better 2-diphenyl-1-picryl-hydrazyl (DPPH), scavenging activity than P. tetragonolobus with IC50 values of 174.380 and 262.313, respectively, as compared to that of the standard, ascorbic acid, IC50 value of which being 111.16. The FRAP assay results for both the plants indicated that the methanol fractions showed closer results when compared with standards, ascorbic acid and quercetin. The IC50 value of S. indicus, P tetragonolobus, ascorbic acid, and quercetin was 70.065, 151.953, 85.162, and 79.647, respectively. These results clearly indicate that S. indicus methanol fraction had better antioxidant activity when compared to both standards. Conclusion: It is concluded that S. indicus and P. tetragonolobus have excellent antioxidant activities which could be the major contributing factors for their medicinal roles. Further studies in this direction are being carried on.